Best Practice Guidance for Effective Methane Recovery and Use from Abandoned Coal Mines - United Nations (United Nations, 2020)
Coal production, transportation, storage and use account for roughly 40% of global greenhouse gas emissions. Methane, which is a potent greenhouse gas with a 100-year global warming potential 25 times that of carbon dioxide (CO2) and a 100-year global temperature potential 6-fold greater than CO2, once released from coal seams in which it is trapped creates number of problems even after cessation of mining activities. Following mine closure, methane emissions decrease, but do not stop completely. They initially decline, but can later stabilize and maintain a near-constant rate for an extended period of time. The document presents recommended principles and standards for effective methane recovery and use from abandoned coal mines in a clear and succinct way, providing decision-makers with a solid base of understanding from which to direct policy and commercial decisions. The Best Practice Guidance does not replace or supersede laws and regulations or other legally binding instruments, whether national or international. The principles outlined therein are intended to complement existing legal and regulatory frameworks and to support development of safer and more effective practices where industry practice and regulation continue to evolve. At the same time, being envisioned primarily as a tool to support performance- and principle-based regulatory programmes, the Best Practice Guidance can also complement more prescriptive regulation and support transition to performance-based regulation.